Effects of iloprost and sildenafil treatment on elabela, apelin-13, nitric oxide, and total antioxidant and total oxidant status in experimental enzyme-positive acute coronary syndrome in rats. (17th February 2020) - Aydin, S.; Kuloglu, T.; Aydin, Y.; Yalcin, M. H.; Ugur, K.; Albayrak, S.; Aksoy, A.; Sahin, İ. and Dagli, A. F. and Akkoc, R. F. and Aydin, S.
ABSTRACT: Despite significant advances in medicine, mortality due to cardiovascular disease is not yet preventable. We investigated the amounts of elabela (ELA) and apelin, synthesized by cardiomyocytes, and changes of these compounds in cardiac tissue and circulation after administration of iloprost (ILO) and sildenafil (SIL) in rats with induced myocardial ischemia (MI). We also investigated a connection with circulating troponin-I, creatine kinase (CK), creatine kinase-myocardial band (CK-MB) and nitric oxide (NO), and total anti-oxidant (TAS)/total oxidant status (TOS). We established eight study groups of five rats each. Group 1, sham, was given only physiologic serum; group 2, ILO; group 3, SIL; group 4, ILO + SIL; group 5, MI; group 6, MI + ILO; group 7, MI + SIL; group 8, MI + ILO + SIL. Troponin-I, CK, CK-MB and TAS-TOS were investigated using an autoanalyzer. NO, ELA and apelin were analyzed by ELISA. Tissue apelin and ELA expressions and localizations were determined by immunohistochemistry. The MI group compared to the control (sham) group showed that ELA, apelin, troponin-I, CK, CK-MB, NO and TOS levels were elevated significantly. Concentrations of these factors increased in MI, but decreased after ILO and SIL administration. The largest decrease of TOS was identified in the ILO + SIL group. ELA and apelin may be novel indicators of MI and administration of ILO and SIL, individually or together, may be useful for treating MI.